Examining of Travel Habits During the Fourth and Fifth Waves of the COVID-19 Pandemic - Rimoczi, Csilla; Jager, Viktor; Beatrix, Lenkovics (European Scientific Journal, ESJ, 2023)
Due to changes in the structure and system of the consumer society, the previously used consumer, geographical and demographic characteristics did not prove sufficient for the exploration and analysis of consumer habits of, and reasons behind, tourism behaviour. As a result, the characterisation of traditional consumer behaviour was complemented by psychological and psychographic factors. These factors also include lifestyle and motivation. As part of a quantitative study based on an online survey, we surveyed regular travellers and Hungarian people interested in travelling. The aim of the research was to arrange the measured sample of travellers into homogeneous groups based on their tourism motivation, lifestyle, and travel behaviour related to COVID19. We also aimed to describe and characterize the resulting groups of travellers based on their well-identifiable characteristics. The study was conducted as a continuation of foundational research. Previous research analysed the impact of the first three waves of the COVID-19 pandemic on travel behaviour. The results of the present research refer to the effects of the fourth and fifth waves.